OCCURRENCE OF THE DEEP SEA STING RAY, UROTRYGON DAVIESI WALLACE IN INDIAN WATERS - Nair, R V; Soundararajan, R (Indian Journal of Fisheries, 2011)
The deep sea sting-ray, Vretrygon daviesi Wallace, caught off Mandapamin the Gulf of Mannar, is recorded for the first time from the Indian waters.A detailed description of the fish, based on a young female, 534 mm in length,is given.